IMMU-31. QUANTITATIVE EVALUATION OF ROUTES OF ADMINISTRATION OF IMMUNOTHERAPEUTIC T CELLS TO ORTHOTOPIC GLIOMA. (9th November 2020) - Hoang-Minh, Lan; Rivera-Rodriguez, Angelie; Pohl-Guimarães, Fernanda; Currlin, Seth; Von Roemeling, Christina; Castillo-Caro, Paul; Otto, Kevin; Rinaldi, Carlos; Mitchell, Duane
Abstract: SIGNIFICANCE: Adoptive T cell therapy (ACT) has emerged as the most effective treatment against advanced malignant melanoma, eliciting remarkable objective clinical responses in up to 75% of patients with refractory metastatic disease, including within the central nervous system. Immunologic surrogate endpoints correlating with treatment outcome have been identified in these patients, with clinical responses being dependent on the migration of transferred T cells to sites of tumor growth. OBJECTIVE: We investigated the biodistribution of intravenously or intraventricularly administered T cells in a murine model of glioblastoma at whole body, organ, and cellular levels. METHODS: gp100-specific T cells were isolated from the spleens of pmel DsRed transgenic C57BL/6 mice and injected intravenously or intraventricularly, after in vitro expansion and activation, in murine KR158B-Luc-gp100 glioma-bearing mice. To determine transferred T cell spatial distribution, the brain, lymph nodes, heart, lungs, spleen, liver, and kidneys of mice were processed for 3D imaging using light-sheet and multiphoton imaging. ACT T cell quantification in various organs was performed ex vivo using flow cytometry, 2D optical imaging (IVIS), and magnetic particle imaging (MPI) after ferucarbotran nanoparticle transfection of T cells. T cell biodistribution was also assessed in vivo using MPI. RESULTS: Following T cell intravenous injection, the spleen, liver, and lungs accounted for more than 90% of transferred T cells; the proportion of DsRed T cells in the brains was found to be very low, hovering below 1%. In contrast, most ACT T cells persisted in the tumor-bearing brains following intraventricular injections. ACT T cells mostly concentrated at the periphery of tumor masses and in proximity to blood vessels. CONCLUSIONS: The success of ACT immunotherapy for brain tumors requires optimization of delivery route, dosing regimen, and enhancement of tumor-specific lymphocyte trafficking and effector functions to achieve maximal penetration and persistence at sites of invasive tumor growth.